On the Perceptual Subprocess of Absolute Pitch - Kim, Seung-Goo; Knösche, Thomas R. (Frontiers in Neuroscience, 2017)
Absolute pitch (AP) is the rare ability of musicians to identify the pitch of tonal sound without external reference. While there have been behavioral and neuroimaging studies on the characteristics of AP, how the AP is implemented in human brains remains largely unknown. AP can be viewed as comprising of two subprocesses: perceptual (processing auditory input to extract a pitch chroma) and associative (linking an auditory representation of pitch chroma with a verbal/non-verbal label). In this review, we focus on the nature of the perceptual subprocess of AP. Two different models on how the perceptual subprocess works have been proposed: either via absolute pitch categorization (APC) or based on absolute pitch memory (APM). A major distinction between the two views is that whether the AP uses unique auditory processing (i.e., APC) that exists only in musicians with AP or it is rooted in a common phenomenon (i.e., APM), only with heightened efficiency. We review relevant behavioral and neuroimaging evidence that supports each notion. Lastly, we list open questions and potential ideas to address them.